First impressions of digital pitches, innovation, and venture funding performance: An evolutionary psychology approach - Joshua D. Maurer; Steven A. Creek; Thomas H. Allison; Joshua S. Bendickson; Arvin Sahaym (Journal of Innovation & Knowledge (JIK), 2025)
We draw from evolutionary psychology to predict that the immediate recognition of certain traits significantly impacts funding outcomes. Four such traits that are recognizable in potential entrepreneurs and play a role in funding decisions are: aggressiveness, attractiveness, competence, and trustworthiness. These initial impressions guide the behavior and decision-making processes of funders. We hypothesize that immediate trait assignments shape initial interpretations, lead to further investigation, and represent qualities that funders view positively or negatively when deciding which campaigns to back. These hypotheses are tested using the first ten seconds of entrepreneurial pitch videos in the crowdfunding context. Our results suggest that these evolutionary-driven traits play a crucial role in funder perception and crowdfunding success and, specifically, that entrepreneurs benefit from displaying aggressiveness and competence in pitches.
Keywords: L26; M13; 650; Entrepreneurship; Crowdfunding; Evolutionary psychology; First impressions